Intensity Measurement of Backscattered Light from Underwater Targets Using Femtosecond Pulse Laser. Issue 3 (4th May 2019) - Zhai, Xiaoyu; Meng, Zhaopeng; Wei, Jianguo; Zhang, Kai; Zhang, Haoyun; Wang, Zhiyang; Qian, Zhiwen
Abstract: In this paper, we experimentally perform the measurement of the backscattered light intensity from the underwater targets with different size. We develop a simple system, which can easily measure the intensity of the backscattered light, after the laser is scattered at the target underwater. We find that, the signal period is related to the particle size, and the stability of the intensity (standard deviation) varies linearly with changing the particle size. After the calibration, our system can be used to precisely determine the particle size of arbitrary targets. Our method could open a new opportunity for the future underwater detection using femtosecond pulse laser.